Grammatical Errors in Writing Narrative Text at SMP Negeri 1 Secanggang - Neneng Sri Lestari (Journal of Classroom Action Research, 2023)
This study entitled Grammatical Error in Writing Narative Text at SMP Negeri 1 Secanggang, is an attempt to identify, classify, and analyze the types of errors in narrative composition produced by students of SMP Negeri 1 Secanggang. This research contributes to the understanding of error analysis, especially narrative composition errors. Ellis's theory was used to analyze errors in students' narrative composition. Data were taken from 34 students of class XI SMP Negeri 1 Secanggang by asking them to write a narrative essay at home on a piece of paper about their experiences when they were on vacation. The results of this study indicate that there are three kinds of errors made by students; they are negligence, misinformation, and misordering. Keyword: Narrative Text, Error, Grammatical